Pancasila sebagai Paradigma Pengembangan Ilmu Pengetahuan dan Teknologi (IPTEK) di Indonesia - Kayla Risti Adzani; Adib Hashif Herliansyah; Zaenul Slam (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Science and technology (science and technology) has a strategic role in encouraging the progress of the nation, but its development needs to be directed so that it is not separated from moral and humanitarian values. Without a strong ethical foundation, the advancement of science and technology has the potential to cause various social problems, such as inequality of access to technology, misuse of technology, and degradation of human values. In the Indonesian context, Pancasila as the basis of the state and the nation's outlook on life can be used as a paradigm in the development of science and technology that is oriented towards humanity, unity, democracy, and social justice. This research aims to examine the role of Pancasila values in building science and technology ethics in Indonesia. The method used is a qualitative approach with literature study techniques on various academic sources, public policy documents, and relevant laws and regulations. The results of the study show that Pancasila values are able to become an ethical foundation in the development of science and technology, so that technological progress is not only oriented to technical and economic aspects, but also to moral responsibility, social justice, environmental sustainability, and the welfare of society as a whole.